Answer: 18x^3-9x^2+21x
Solution:
3x(6x^2-3x+7)=
Applying the distributive property in the multiplication to eliminate the parentheses:
(3x)(6x^2)+(3x)(-3x)+(3x)(7)=
(3*6)x^(1+2)+3*(-3)x^(1+1)+(3*7)x=
18x^3-9x^2+21x
Answer: 27.2
Step-by-step explanation:
A squared + B squared = C squared 22 is A squared and 16 is B squared and C squared is the hypotenuse and that is what we are figuring out
22squared= 484 and 16 squared=256 484+256=740 and 27.2 squared is 740 I hope this helps
234 - 3 = 231
231 : 3 = 77
77 + 1 =78
78 + 1 = 79
------------------------
77 78 79
77+78+79= 234
Answer:
5
Step-by-step explanation:
b^2= (5)^2 = 25
So.... b=5 or -5
......
Step-by-step explanation:
d=2r=12
c=12π=37.69